Correlation between local monocarboxylate transporter 1 (MCT1) and glucose transporter 1 (GLUT1) densities in the adult rat brain - Maurer, Martin H.; Canis, Martin; Kuschinsky, Wolfgang; Duelli, Roman (Neuroscience letters, 2004)
Monocarboxylate transporters type 1 (MCT1) facilitate the transport of monocarboxylates across cell membranes of the blood-brain barrier and brain parenchymal cells. The present study had two aims: (1) to determine the local distribution of MCT1 in the brain; and (2) to compare the local densities of MCT1 with the local densities of the main nutritional transporters, glucose transporter GLUT1. Using immunoautoradiography of cryosections from rat brain, 32 brain structures were analyzed. (1) A heterogenous distribution pattern of MCT1 densities was observed throughout the brain. Compared to brain homogenate (100%), MCT1 densities ranged from 43 to 164% in the brain structures investigated. Local GLUT1 densities showed a comparable range (35-145%). (2) A close correlation was found between local MCT1 and local GLUT1 densities. As local GLUT1 densities reflect local glucose metabolism in the brain, we conclude that local MCT1 densities are adjusted to local glucose metabolism and transport.